Modified method of safe storage of hard coals with increased self-ignition tendency’s - Róg , Leokadia (Instal, 2019)
The necessity to store coal in coal dumps results, among others, from the obligation for power plants to maintain hard coal reserves necessary to maintain continuity in the process of electricity and heat production. The principles of hard coal storage are regulated by PN-G-07010:1994 „Hard coal and hard coal briquettes. Storage” standard. The guidelines described in it, clearly differentiate the way of handling coals with low self ignition tendency from the handling of coals with high self-ignition tendency. The propensity of Polish energetic coals to sefl-ignition is varied. In order to determine this diversity, tests were conducted for 70 samples taken from coal fines, classified according to the Polish classification, in accordance with the standard PN-82/G-97002 [8], for types from 31.1 to 34.2. Studies have shown a good correlation between activation energy, which characterizes the tendency of coal to self ignite and the degree of carbonization of organic carbon, expressed by vitrinite reflectance (Ro). As the vitrinite reflectance index increases, the coal’s self-ignition tendency decreases.
Keywords: hard coal; storage; self-ignition; compaction method